The Role of Computer Simulation Impact for Sustainable Development in Engineering Experiments: Mini Review - Hosan, Shen; Perera, Hasith; vithanage, Vimukthi; Wijesekara, Dasith; Kelum, Anjula; koswattage, kaveenga (RADINKA JAYA UTAMA PUBLISHER, 2025)
Sustainable development has become a foundational principle in modern engineering research and practice. Conventional physical experiments frequently require considerable resource utilization, produce waste, and demand substantial time, thereby presenting obstacles to environmental objectives. This paper aims to evaluate the impact of computer-based simulations as a transformative approach to engineering experiments, specifically examining how they align with sustainability goals compared to conventional methods. This study employs a mini-review methodology, synthesizing data from various case studies across engineering disciplines. The analysis focuses on three primary sustainability metrics: resource efficiency, environmental impact reduction, and temporal optimization. The findings demonstrate that computer simulations drastically reduce the carbon footprint of research by minimizing the need for physical prototypes and hazardous materials. Furthermore, simulations allow for rapid iterative testing, which fosters innovation while ensuring high experimental rigor. Case studies show that integrating simulation tools can lead to a significant decrease in material waste up to 60-80% in certain manufacturing and structural testing scenarios. Conclusion: This study concludes that computer-based simulations are not merely a technical convenience but a critical driver for sustainable development in engineering. By maintaining experimental scrupulousness while enhancing efficiency, simulations provide a viable pathway for future-proof engineering practices that balance technological progress with environmental responsibility.